1087. COVID-19 in Solid Organ Transplant Recipients: A Single Transplant Center Experience. (15th December 2022) - Sabunwala, Suhel A; Cornelius, Tuhina; Aslam, Sadaf; Alrabaa, Sally
Abstract: Background: COVID-19 disease became a global health care crisis and was declared pandemic by WHO in March 2020. Some studies have indicated that Solid Organ Transplant (SOT) patients may have increased morbidity and mortality while others showed no difference. Our study aims to investigate patients' characteristics, disease course, management of COVID-19 and outcomes in our SOT patient population. Methods: We conducted a retrospective cohort study of all consecutive SOT recipients who were admitted to our transplant center from March 2020 to April 2021 with COVID-19 infection. Data was collected from the electronic medical records after receiving Institutional Review Board approval. Table 1 Study Population Demographics Figure 1 Age and Gender distribution of the study population Results: A total of 135 patients met inclusion criteria. Average age at the time of COVID-19 diagnosis was 56.38±12.93 years. Majority of the patients (54%) were kidney transplant recipients. Out of the total, 28% of the patients required supplemental oxygen and 14% required intensive care unit (ICU) care. A total of 12 patients (9%) required intubation and mechanical ventilation. 21% of the patients were treated with Remdesivir and 30% met criteria for the use of corticosteroids. Unfortunately, 11 patients (8%) of the patients died from COVID-19 infection and its complications. Of those 11 patients 5 were treated with Remdesivir and 10 were treated Corticosteroids. None of the patients met the criteria for ECMO (Extra Corporeal Membrane Oxygenation). Figure 2 Study Population Distribution of the Types of Transplants at time of COVID-19 infection Figure 3 Outcomes - Admission to ICU and Mortality Figure 4 COVID-19 Therapies and Outcomes in the SOT Recipients Conclusion: Our study showed a higher mortality rate in SOT patients compared to general population. Treatment with Remdesivir and Corticosteroids improved the overall mortality rate but had no benefit in patients with critical illness requiring ICU level care. COVID vaccination significantly improved the outcome, and the major limitation of the study was COVID vaccination information was not included since the study was initiated prior to introduction of vaccines. More studies with larger sample size and vaccine data need to be conducted to accurately determine the outcome of COVID-19 infection in this patient population. Disclosures: All Authors : No reported disclosures.